PENGARUH MOTIVASI INDIVIDUAL TERHADAP KINERJA PEGAWAI PADA KANTOR KELURAHAN TANAH GROGOT - Harmayanto Harmayanto; Amir Hamzah (Jurnal Ilmiah Ekonomika & Sains, 2020)
The formulation of the problem in writing this thesis is: is there an influence of individual motivation consisting of the need for achievement, the need for affiliation, and the need for power. And which variable among the individual motivational variables has the dominant influence on employee performance. The benefit to be achieved in this research is that it can be used to improve employee performance in the future. From the results of multiple linear regression analysis, we get the function equation Y = 2.224+0.119X1+0.141X2+0.245X3. From these results it can be seen that individual motivation variables have a positive effect on employee performance at the Tanah Grogot Village office. This effect is also explained by the R2 value (coefficient of determination) of 0.495, which means that the variables studied have an effect of 49.5% and the remaining 50.5% is influenced by other variables not included in this study. The regression coefficient (R), which describes the strong relationship between the independent variables and the dependent variable can be seen in the test, which is equal to 0.734. This means that there is a strong relationship between the independent variable and the dependent variable. Fcount value ˃ Ftable or 12.088 ˃ 2.9113 and probability value 0.000 ˂ 0.05. Shows that individual motivation variables have a simultaneous (together) effect on employee performance. Of the individual motivational variables, the variable need for achievement gives a dominant influence, this is evidenced by the value of tcount ˃ ttable or 3.521 ˃ 1.6955 and the smallest probability value is 0.001 ˂ 0.05 Seeing the results of the discussion above, it is concluded that the initial hypothesis proposed is accepted, because the initial hypothesis states that the dominant variable is the variable need for achievement (X1).